Contribuição ao Conhecimento Químico de Plectranthus ornatus Codd - Ávila, Fábio do Nascimento (2015)
The present work describes the phytochemical and pharmacological study of aerial parts of Plectranthus ornatus Codd (Lamiaceae), cultivated at Horto de Plantas medicinais da Universidade Federal do Ceara-UFC. P. ornatus is a native plant from India, introduced in Brazil during the age of great navigations and used by the folks as a relief and treatment of digestive and respiratory problems by the name of boldo-gambá, boldo pequeno and novalgina. The hexane extract of aerial parts of P. ornatus were submitted to successively chromatographic process, including High Performance Liquid Chromatography (HPLC), obtained eleven (11) chemical compounds belonging to diterpene class, which five (05) are described for the first time on literature and named as: Methyl-11R-acetoxyneocleroda-3,13E-dien-15-oic, 11R-acetoxy-3,4-dihydroxyneocleroda-13E-en-15-oic acid, 11R-acetoxysolidagonal acid, 11R-acetoxy-solidago-3,15-dioic acid, Pseudo-coleon R and 11R-acetoxyneocleroda-2,4(18), 13E-trien-15-oic acid, together with six (06) known compounds: Plectrornatin A, Coleon R, ent-labd-13-en-8β-ol-15-oic acid, 11R-acetoxy-3β-hydroxyneocleroda-4(18), 13E-dien-15-oic acid and 11R-acetoxy-2-oxo-neocleroda-3,13E-dien-15-oic acid. The structure determination of all secondary metabolites isolated was performed by spectrometric techniques such as hydrogen-1 and carbon-13 nuclear magnetic resonance (1H NMR and 13C one/two- dimensional), infrared spectrometry (IR), high resolution mass spectrometry and comparison with literature data. Cytotoxic activity of compounds was evaluated against four different human cancer cell lines: HCT-116 (colon adenocarcinoma), HL-60 (leukemia), OVCAR-8 (ovarian carcinoma) and SF-295 (glioblastoma). The cell cultures were regularly maintained at logarithmic phase of growth. IC50 values were determined using the MTT assay and measured IC50 values along with 95% confidence.